2020
DOI: 10.1155/2020/4323989
|View full text |Cite
|
Sign up to set email alerts
|

Korean Traditional Medicine in Treating Patients with Mild Cognitive Impairment: A Multicenter Prospective Observational Case Series

Abstract: In Korea, patients with mild cognitive impairment can choose to receive treatment of Korean medicine, and Korean medicine hospitals provide specialized medical care for the prevention and management of cognitive disorders. The aim of the study is to explore the role of Korean medicine therapy for patients with mild cognitive impairment in a real clinical setting. Fifteen patients with amnestic mild cognitive impairment were enrolled in this prospective observational study in three Korean medicine hospitals. Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Alzheimer's disease (AD) is the most common form neurodegenerative disease accompanying progressive memory and cognitive impairment [1][2][3]. The accumulation of senile plaques composed by the aggregated β-amyloid (Aβ), formation of neurofibrillary tangle as aggregates of phosphorylated tau protein, and progressive loss of cholinergic neurons and nicotinic acetylcholine receptors have been characterized as main pathological features of AD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's disease (AD) is the most common form neurodegenerative disease accompanying progressive memory and cognitive impairment [1][2][3]. The accumulation of senile plaques composed by the aggregated β-amyloid (Aβ), formation of neurofibrillary tangle as aggregates of phosphorylated tau protein, and progressive loss of cholinergic neurons and nicotinic acetylcholine receptors have been characterized as main pathological features of AD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory agencies (e.g., FDA, EMA, etc.) suggest that the evaluation of the pharmacokinetic herb-drug interactions [37][38][39][40], as well as of PK-based HDIs (e.g., herbal product combinated with donepezil as a drug for AD treatment), is also necessary [3,41].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used licensed herbal medicine products manufactured by pharmaceutical companies that were produced according to the Korean Herbal Pharmacopoeia (KHP), and modification of compositional herbs was not possible. Therefore, the use of frequently added herbs for cognitive disorders, such as Acori Graminei Rhizoma and Polygalae Radix 32–34 was difficult. In this study, the patients’ cognitive functions generally improved after the herbal medicine treatment, even without those herbs.…”
Section: Discussionmentioning
confidence: 99%
“…herbs was not possible. Therefore, the use of frequently added herbs for cognitive disorders, such as Acori Graminei Rhizoma and Polygalae Radix [32][33][34] was difficult.…”
mentioning
confidence: 99%
“…In addition, there has been a belief that it is difficult to derive social and medical contributions as much as synthetic medications. Recent scientific research, on the contrary, has indicated that the combinatorial effect of mixed EAHM preparation can be particularly effective for complicated disorders, such as PN, autoimmune disease, degenerative disease, and cancer, which do not react well with single compound-based modern pharmaceutics [121][122][123][124]. As an example, recent research has demonstrated that EAHM can be used in large-scale public health emergencies, such as COVID-19 or preventive medicine using modern analytical tools, such as synthetic biology, data mining, and genomics [123,[125][126][127][128].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%